Anthelmintics in the Aquatic Environment: A New Analytical Approach - Kumirska, Jolanta; Wagil, Marta; Stolte, Stefan; Maksymiuk, Monika; Puckowski, Alan; Maszkowska, Joanna; Biak-Bieliska, Anna; Caban, Magda; Stepnowski, Piotr (Current Analytical Chemistry, 2016)
Anthelmintics are intensively used for veterinary treatment and after being released into the environment can ultimately pose environmental and health hazards. However, to date, there has been very limited information on the concentrations of anthelmintics in the aquatic environment. The monitoring of these compounds in different compartments (water, sediment and fish tissue samples) is crucial if a thorough risk assessment is to be made. In this study, such an analytical approach is presented for the first time. As model compounds, two benzimidazoles: flubendazole (FLU) and fenbendazole (FEN), and doramectin (DOR) representing avermectins, were selected. As a model aquatic environment - the Reda river in northern Poland was chosen. The water, sediment and fish tissue samples were collected in 2014, the sediments were also collected in 2013. All of the compounds were detected at least once in the survey. All of the risk quotients, apart from DOR in waters, were lower than 1, thus no risk to the environment can be derived from these results. However, in the case of DOR, such a risk was observed. The results were compared with those published for Poland and other countries. In summary, the simultaneous determination proposed here of anthelmintics in different compartments, significantly improves the environmental risk assessment of this class of drug.
Keywords: environmental risk assessment